Pengaruh Motivasi Kerja dan Fleksibilitas Kerja Terhadap Kinerja Driver Grabbike di Kota Cirebon - Sarno; Wiwi Hartati; Mery Sukartini (INDO PUBLISHING, 2025)
This study investigates the influence of work motivation and job flexibility on the performance of GrabBike drivers in Cirebon City. The research emphasizes how intrinsic drive and flexible work arrangements affect service quality and operational outcomes in the gig economy. The research was conducted on 290 GrabBike drivers in Cirebon using a quantitative approach with an associative method. Data were collected through a structured questionnaire. The sampling technique used was incidental sampling. Data analysis was performed using SPSS version 25.0, applying validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, and F-tests to examine the influence of each variable. Results indicated that work motivation and job flexibility both positively and significantly affect GrabBike driver performance, both individually and simultaneously. The combination of intrinsic motivation and flexible work rhythms enhances performance, confirming that these variables play a crucial role and contribute to theory and practice in gig economy human resource management. The study concludes that the synergy between intrinsic motivation and flexible work conditions fosters optimal performance among GrabBike drivers, reinforcing the importance of human resource strategies tailored to the gig economy. This study only covers drivers operating in Cirebon and uses self-reported data, which may be subject to bias or limited generalizability to other regions or platforms. This study contributes to human resource management by demonstrating the pivotal role of motivation and flexibility in digital labor platforms. Its findings benefit platform managers, HR practitioners, and researchers in labor economics and organizational behavior..